2003
DOI: 10.2175/106143003x140863
|View full text |Cite
|
Sign up to set email alerts
|

Making Classifying Selectors Work for Foam Elimination in the Activated‐Sludge Process

Abstract: Classifying selectors are used to control the population of foam-causing organisms in activated-sludge plants to prevent the development of nuisance foams. The term, classifying selector, refers to the physical mechanism by which these organisms are selected against; foam-causing organisms are enriched into the solids in the foam and their rapid removal controls their population at low levels in the mixed liquor. Foam-causing organisms are wasted "fi rst" rather than accumulating on the surface of tanks and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…Confirming work showed that an anaerobic selector seemed quite effective for nocardioform control, when combined with SRT control and with sufficiently low SRT (Jolis et al, 2005). Due to the high level of foam trapping in the compartmentalized HPOAS system, a classifying selector was only partly successful at Sacramento in its first HPOAS application (Parker et al, 2003b), but proved to be quite reliable when combined with other measures in a later San Francisco trial (Jolis et al, 2006).…”
Section: The High Purity Oxygen Activated Sludge Processmentioning
confidence: 95%
See 2 more Smart Citations
“…Confirming work showed that an anaerobic selector seemed quite effective for nocardioform control, when combined with SRT control and with sufficiently low SRT (Jolis et al, 2005). Due to the high level of foam trapping in the compartmentalized HPOAS system, a classifying selector was only partly successful at Sacramento in its first HPOAS application (Parker et al, 2003b), but proved to be quite reliable when combined with other measures in a later San Francisco trial (Jolis et al, 2006).…”
Section: The High Purity Oxygen Activated Sludge Processmentioning
confidence: 95%
“…This work put into better perspective what DO levels were appropriate for each process to prevent high F/M and low DO bulking. What followed were two decades of work on progressive improvements to bulking control in conventional activated sludge systems with improved reliability through the use of selectors (see Jenkins et al, 2004and Parker et al, 2003a, 2003b. This indirectly muted the argument that the HPOAS process produced mixed liquor with significantly better compaction and settleability.…”
Section: The High Purity Oxygen Activated Sludge Processmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, only foam removal is discussed, rather than providing for a selector for foam elimination. In fact the single reference to our work in MOP 8 (page 14-213), states " Parker et al (2003) introduced the concept of adding mechanical skimming devices, such as a spiral or chain-and-flight blades to move floatables up a beach and into a hopper located at the end of the aerated channel." This fails to accurately and completely describe our work as the selection mechanism is not described nor are its mechanical features (we have never used any of the MOP 8 described equipment in our Classifying Selector designs).…”
Section: Figure 4 Classifying Selector Design Was Successful At El Pmentioning
confidence: 99%
“…When designing inter-zone baffles it is important to provide a head loss which allows surface foam to pass freely. Since selectors have not generally provided consistent elimination of foam causing organisms, we have developed and provided classifying selectors at strategic locations within the reactor to eliminate or control foam-causing organisms, and thus avoid deterioration of effluent quality (Parker et al, 2003).…”
Section: Influence Of Selector On Effluent Qualitymentioning
confidence: 99%